Learning to Engage Children: Towards a model for Undergraduate Students in Nursing - a Grounded Theory study - Coetzee, Minette (Nursing, 2017)
In South Africa, paediatric nursing practice has traditionally been seen as a speciality. Yet in 1998, while a staggering 45% of the population were younger than 18 years, still only 2.4 % of all registered nurses held a Paediatric qualification1 and the reality of the size of the population of children, continued to impact Health Service provision. The challenge of facilitating undergraduate students learning a traditionally post-basic nursing discipline led to this study in the Department of Nursing at the University of Cape Town. Here the philosophical approach is health based; whole-person orientated and family centred and the programme includes a distinct children's nursing component. The purpose of the study was to discover how student nurses learn to nurse children. Participants came from four consecutive student groups in their third year of undergraduate study. The use of grounded theory methodology allowed a rich understanding of the process to emerge. Data included participant observation and student descriptions, both private in reflective journals and narratives and corporate, in focus groups. In the wealth and variation of experience and learning, analysis of data confirmed the complex relational nature of students' learning. The relationships students establish with the children they encounter in the course of their learning emerged as central to their learning. Findings indicate that puzzling out connection is the students' basic social process in learning to nurse children. Students' experiences of childhood and parenting influence their expectations, interactions and application of learning. The various conditions that affect how students choose to engage children have been extensively explored and described. Students in this study engage children in four distinctive modes; which have been described as playful 1 connecting, dutiful safeguarding, in relay with the child's mother and distant doing. The findings of this study contribute to the understanding of how students learn to nurse, especially in the life stage of late adolescence. This is essential for structuring the learning environment and experiences of students learning to care for children.